Efficiency of Professional Training of Ethnographic Tourism Managers under Experimental Learning Conditions - Vovchok, Yaroslav (Pedagogical Discourse, 2017)
Efficiency of professional training of future specialists in higher educational institutions is determined by the content of educational material, a set of appropriate methods and forms of organization of students’ educational activities, the competence of teachers, cognitive activity of students and other factors. And it is achieved by applying an integrated approach to the organization of educational process and the training of highly skilled tourism specialists. At the same time, it is important to take into account various aspects of the professional training of future tourism managers when developing and implementing the author’s own model. Conducting experimental research in the system of complex training of future specialists for the organization of ethnographic tourism is an important part that allows to determine and trace the preparedness of students to conduct appropriate tourism activities. The experimental process makes it possible to verify the knowledge and skills acquired and realized by students to design ethnographic tourism. As a result of the experiment, the author’s own model of the training of future managers to organize ethnographic tourism, the effectiveness of its influence on improving and enriching the educational and training program for the ethnographic tourism managers has been reflected. And at the formative stage of the experiment it is important to reveal the processes of formation of the motivational, cognitive, communicative and professional components of the individual. At the professional level, attention is focused on the practical aspects of organizing ethnographic tourism, problems that may arise in future professional activities of tourism managers. Therefore, the following methods and forms of training organization are used: business games, project technologies, professional trainings, as well as the passing of industrial practices at tourist enterprises. The business game is to some extent a simulation of professional activity; in a business game there is a dialogue at the professional level, a collision of different opinions and positions, mutual criticism of hypotheses and proposals, their justification and strengthening, leading to the emergence of new knowledge and ideas, helps to gain experience in professional activities.The author analyzed the possibility of using this experience in order to introduce it into the system of vocational training of the personnel of the tourism industry of Ukraine.